Expeditions & Explorations - Gifford, Nigel (London Macmillan, 1983)
Discusses every aspect of expedition planning, including the conception of the idea, the selection of team members, travel arrangements, sponsorship and finance, and the choice of food and equipment.
Include Pictures and index
Keywords: Scientific Expeditions -- Voyages and Travels